Effect of luteal phase support gonadotropin-releasing hormone agonist on the endometrial receptivity and outcomes of in vitro fertilization programs - E M Savelyeva; S G Perminova; T A Demura; D A Strelchenko (IP Berlin A.V., 2016)
Patients with tubal infertility in implantation window period show impaired endometrial receptivity with low implantation potention that is characterized by decrease in mature pinopodes level on endometrium, decreased expression of leukemia inhibitory factor, gonadotropin-releasing-hormone, gonadotropin-releasing-hormone receptors, HOXA10 gene in epithelium and stroma and disbalancein progesterone and estradiol receptors in stroma. The use of gonadotropin-releasing-hormone agonist for luteal phase support has a favorable impact on endometrial receptivity and clinical outcomes of in vitro fertilization programs.